2023
DOI: 10.3390/ijms241512470
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Continuous Cropping Obstacles and Control Strategies in Medicinal Plants

Muhammad Zeeshan Ul Haq,
Jing Yu,
Guanglong Yao
et al.

Abstract: Continuous cropping (CC) is a common practice in agriculture, and usually causes serious economic losses due to soil degeneration, decreased crop yield and quality, and increased disease incidence, especially in medicinal plants. Continuous cropping obstacles (CCOs) are mainly due to changes in soil microbial communities, nutrient availability, and allelopathic effects. Recently, progressive studies have illustrated the molecular mechanisms of CCOs, and valid strategies to overcome them. Transcriptomic and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 168 publications
0
13
0
Order By: Relevance
“…The main obstacles posed by continuous cropping is the decrease in soil quality, which can include soil compaction, nutrient imbalance, salinization, enzyme activity reduction, and the accumulation of harmful microorganisms [48]. In our study, the physiochemical property indices of the substrates (EC, and OM, TN and TP contents) decreased with continuous cropping.…”
Section: Effect Of Tcm On the Physicochemical Properties Of Substratesmentioning
confidence: 59%
“…The main obstacles posed by continuous cropping is the decrease in soil quality, which can include soil compaction, nutrient imbalance, salinization, enzyme activity reduction, and the accumulation of harmful microorganisms [48]. In our study, the physiochemical property indices of the substrates (EC, and OM, TN and TP contents) decreased with continuous cropping.…”
Section: Effect Of Tcm On the Physicochemical Properties Of Substratesmentioning
confidence: 59%
“…In agricultural practice, the continuous planting of P. cablin on the same land will lead to changes in the soil's physical and chemical properties [52,53], the microbial community structure, the aggravation of soil diseases, and more serious allelopathic autotoxicity, resulting in serious continuous cropping obstacles [54][55][56][57]. Previous studies have found that p-HBA is the main allelochemical that induces continuous cropping obstacles of P. cablin [16,58]. In this study, 30 down-regulated candidate genes and 27 up-regulated candidate genes were identified by analyzing the transcriptome data of P. cablin roots treated with p-HBA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mixed organic acids also increased the content of L-malic and shikimic acid in the biosynthesis of the plant hormones pathway. Previous results have shown that L-malic and shikimic acid could promote the growth of pathogens and the formation of phenolic acid autotoxic substances [3,48,49], respectively. Therefore, the mixed organic acids increased the production of harmful metabolites in Sanqi soil, resulting in the autotoxicity of the mixed organic acids being stronger than that of the single organic acids.…”
Section: Different Types Of Organic Acids Changed Soil Dms and Metabo...mentioning
confidence: 98%